Desempenho dos fundos de investimento de ações brasileiro: um estudo do período de 2000 a 2014 - Pinto, Daniel Mathias Alves (2014)
The primary objective of this work is to answer if Brazilian equity funds were capable of creating value, as measured by Jensen’s alpha, during the selected period. After that it tried to identify the significate factors to value creation. Using the methodology developed by Jensen (1968), funds with significant alphas were separated from funds without them. The market portfolios used as benchmarks were Ibovespa and IBRx and the risk free rates were CDI, Selic and Account Savings (poupança). Regardless of the risk free rate or market portfolio, results obtained indicated that Brazilian equity mutual funds were not capable of generating alphas. Nevertheless, when compared with IBRx, mutual funds’ performance was even worse. After going through this process, a cross section regression was used to find the alpha generating significant variables, and the conclusion was that the larger the fund, the greatest the alpha it would generate. However, the older the fund and the higher the fees, the lower the alpha generated. Finally, for fund managers with positive significant alphas, risk was positively correlated with performance and for the ones with negative significant alphas, risk was negatively correlated with performance